The Correlation Between Spiritual Level and Life Quality of Breast Cancer Patients - Amirudin, Ikhwan; Stiexs, Anggie; Wahyudi, Dian Arif (Universitas Aisyah Pringsewu, 2022)
Good quality of life will provide good physical and spiritual health and will be able to run a life in the community according to their respective roles. The research objective is to determine the correlation between spirituality level with the life quality of breast cancer sufferers. The research type used a quantitative research method with a cross-sectional approach. The measurements used the EORTC QLQ-30 + EORTC BR-23 questionnaire. The research results showed that the spirituality level of sufferers in dealing with breast cancer on average had a high spirituality level of 38 people (84%). There is no correlation between spirituality level with the life quality of breast cancer sufferers this was demonstrated by the results of the analysis of Spearman's Test average p-value of more than 0.05. Abstrack: Kualitas hidup yang baik akan memberikan kesehatan jasmani dan rohani yang baik, serta akan dapat menjalakan hidup didalam masyarakat sesuai perannya masing-masing. Tujuan mengetahui hubungan antara tingkat spiritual dengan kualitas hidup pada pasien kanker payudara. Penelitian kuantitatif ini menggunakan metode penelitian pendekatan cross sectional. Pengukuran menggunakan kuisioner EORTC QLQ-30 + EORTC BR-23. Hasil penelitian menunjukan bahwa tingkat spiritual pasien dalam menghadapi penyakit kanker payudara rata-rata memilik tingkat spiritual yang tinggi yaitu 38 orang (84%). Tidak ada hubungan tingkat spiritual dengan kualitas hidup pasien kanker payudara hal ini ditunjukan dengan hasil analisis uji spearman’s yang rata-rata p value lebih dari 0,05.